Application of Web-technologies in the educational process of higher educational institutions of Ukraine - Olga Potapchuk (Kazimierz Wielki University, 2018)
In the article actuality and features of the use of Web-technologies are exposed in the educational processof higher educational institutions of Ukraine, basic functions that have an influence on forming of professional competence of future specialists are distinguished. The analysis of advantages and laks of application of Web-technologies is conducted in an educational process. Problems that arise up on the way of informatization of education in Ukraine are reflected. It is marked that the uses of all modern technologies areeffective in combination with the traditional form of studiesand assist the quality forming of professional competence of future specialists.